2019
DOI: 10.1007/s11090-019-10039-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Normal Human Skin Cells by a Portable Dielectric Barrier Discharge-Based Reaction-Discharge System of a Defined Gas Temperature

Abstract: Skin injury leading to chronic wounds is of high interest due to the increasing number of patients suffering from this symptom. Proliferation, migration, and angiogenesis are key factors in the wound healing processes. For that reason, controlled promotion of these processes is required. In this work, we present the portable helium-dielectric barrier discharge (He-DBD)-based reaction-discharge system of controlled gas temperature for biological activities. To make this He-DBD-based reaction-discharge system sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Studies using both gas plasma exposure and cerium oxide nanoparticles have not been reported yet. A range of studies are available for silver nanoparticles, demonstrating combined cytotoxicity with gas plasma treatment in Hs 294T human melanoma cells [ 57 ] and even antimicrobial efficacy in bacterial phytopathogens [ 58 ]. Gas plasma exposure in glioblastoma cells also led to enhanced silver nanoparticle uptake rates and enhanced cytotoxicity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using both gas plasma exposure and cerium oxide nanoparticles have not been reported yet. A range of studies are available for silver nanoparticles, demonstrating combined cytotoxicity with gas plasma treatment in Hs 294T human melanoma cells [ 57 ] and even antimicrobial efficacy in bacterial phytopathogens [ 58 ]. Gas plasma exposure in glioblastoma cells also led to enhanced silver nanoparticle uptake rates and enhanced cytotoxicity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the CAPP-activated media, including the DMEM and the Opti-MEM, a CAPP-based reaction-discharge system, previously developed and optimized in our research group, was used [ 33 ]. In this CAPP-based reaction-discharge system, a DBD plasma jet is sustained in He and used as a CAPP source.…”
Section: Methodsmentioning
confidence: 99%
“…The optimal operating conditions of this reaction-discharge system, leading to the CAPP-activated media production, were as follows: The frequency of the modulation: 2.14 kHz; the duty cycle: 74.29%; and the He flow rate 10.6 L min −1 . Under these optimal operating conditions, the gas temperature (based on the OH (0-0) radical emission spectrum) was about 37 °C (310 K) [ 33 ]. The additional electrical parameters, i.e., the voltage amplitude, the voltage waveform shape, and the general frequency, were assessed using a digital two-channel storage oscilloscope (Tektronix, TBS 1000, Beaverton, OR, USA) and were as follows: (i) the voltage amplitude: 6 kV; (ii) the voltage waveform: square wave; and (iii) the general frequency: 66.45 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the discharge parameters of the applied NTAPP, such as the amplitude of voltage, the duty cycle, and the flow rate of the discharge gas, should have been fully optimized prior to use. Having this in mind, we focused on the DBD-generating portable device that we previously constructed and studied for medical purposes [29]. As NTAPP remains the source of an electromagnetic field, heat radiation as well as UV photons, we investigated whether the DBD exposure causes a physical damage to the plant material or alters the germination-associated properties of mung bean seeds.…”
Section: Impact Of Dbd Treatment On Germination Rate and Early Growth Of Mung Bean Seedlingsmentioning
confidence: 99%